Konwergencja realna fundamentem powodzenia integracji monetarnej Polski ze strefą euro - Tomczak-Woźniak, Ewa (Lodz University of Technology Press, 2015)
Celem opracowania jest prezentacja wniosków z analizy poziomu realnej konwergencji Polski z gospodarką Eurolandu W opracowaniu podjęto również próbę analizy kosztów i korzyści przyjęcia euro, a także potencjalnych szans i zagrożeń związanych z funkcjonowaniem w europejskiej unii monetarnej Na koniec zawarto też wstępne wnioski na temat znaczenia kryzysu finansowego lat 2007-2010 dla perspektyw przyjęcia w Polsce waluty euro.

The aim of the study is a presentation of conclusions from analysis of the level of the real convergence of Poland with the economy of Euroland. In the study was also made an attempt of the cost-benefit analysis of the adoption of the euro, as wel1 as potentia! chances and threats associated with functioning in the European monetary union. In the end of the study there are also preliminary conclusions about meaning of the financial crisis of 2007-2010 years for prospects of taking the euro-currency in Poland.
Real convergence as a foundation of the success of monetary integration of Poland with the euro zone